Influence of post-migration living difficulties on mental health among refugees and asylum seekers: A scoping-review on clinical tools - Santambrogio, Jacopo; Cimminiello, Noemi; Wisidagamage Don, Prasad; Leon, Elisabetta; Miragliotta, Elena; Capuzzi, Enrico; Colmegna, Fabrizia; Clerici, Massimo (International journal of social psychiatry, 2024)
Background: The literature indicates an increasing interest in the mental health of refugees (R) and asylum seekers (AS) – particularly how it could be affected by previous exposure to trauma and violence – but less has been written about the issues they are forced to face during the post-migration period and how these also can affect mental health. Research shows that the mental health of R/AS is highly influenced by their post-migration conditions and may deteriorate due to post-migration social health-related determinants; in addition, a lack of language skills, discrimination, separation from family, poverty, and other stressors can contribute to social isolation. The difficulty in asking for help in case of psychological distress and, consequently, in accessing care, contributes to the worsening of their clinical condition. Aims: The primary purpose of this study is to identify and provide a review of the clinical tools used to screen migrants (R/AS) at risk of developing psychological distress, identifying post-migration difficulties. Methods: We searched studies in PubMed, Embase, Scopus, Cochrane (Central), and Cinahl (ultimate) with the last search on 14 April 2023, using a combination of keywords and Medical Subject Headings (MeSH). Results: Our systematic search identified 1,878 records. After removing duplicates, we screened 1,238 records by title and abstract, retaining 97 for full text review. Of these, 68 met full eligibility criteria (1995–2023). A total of 30 social scales have been identified, as well as structured or semi-structured questionnaires and interviews. Translated into multiple languages, the tools can be self-administered or administered by trained professionals. PMLD is known for its effectiveness in evaluating the post-migration period and predicting mental health issues. Conclusions: Considering the limited number of studies and, consequently, the limited number of tools found, it can be inferred that not enough attention is given to post-migration in the broader sense.